Housing development and management - Ghosh, Santosh; Gupta, Ranajit; Gupta, Sumita (Centre for Built Environment, 1996)
Papers presented at the International Workshop on Housing Development & Management organized by Centre for Built Environment, held in December 9-11, 1994 at Calcutta.